Broadband, High‐Efficiency and Wide‐Incident‐Angle Anomalous Reflection in Groove Metagratings. Issue 9 (28th June 2021) - Liu, Chuanbao; He, Jingjin; Zhou, Ji; Xu, Jianchun; Bi, Ke; Chen, Junhong; Qiao, Lijie; Bai, Yang
Abstract: In this paper, some nonplanar metagratings with multilevel asymmetric grooves are demonstrated to produce broadband and high‐efficiency anomalous reflection in wide‐incident‐angle range. First, bipartite metagrating with two asymmetric grooves per unit cell is proposed and optimized by machine learning. It can not only realize a high efficiency (≈88.8%) and large‐angle (≈70°) anomalous reflection under normal incidence, but also preserve the high performance over broad bandwidth (12.0–20.0 GHz) and wide‐incident‐angle range. Furthermore, to improve the large‐angle anomalous reflection at low frequencies, a tripartite metagrating is designed. The participation of more cavity modes makes the metagrating achieve the anomalous reflection with an efficiency greater than 90% over a broader bandwidth from ±1st Rayleigh anomalies to 20.0 GHz (even higher) and a wide range of incident angles from −70° to 70°, which is verified by the experimental measurement. Especially at an incident angle of 20°, the high‐efficiency anomalous reflection is sustained over an ultrabroad frequency range from 9.7 to 21.2 GHz, i.e., a fractional bandwidth of 74.4%. The excellent performance of anomalous reflection and relatively simple structures endow the asymmetric groove metagratings with abundant functions, such as ideal three‐channel retroreflector and abnormal reflector, and make them attractive in highly efficient and extreme wave manipulation. Abstract : In this paper, by using the constructive interference of fundamental cavity modes, multilevel asymmetric groove metagratings are proposed to demonstrate a broadband and high‐efficiency anomalous reflection no matter for normal incidence or oblique incidence. The excellent properties and simple configuration endow metagratings with ideal three‐channel retroreflector and abnormal reflector, and make them attractive in highly efficient and extreme wave manipulation.